Toxicity of wine effluents and assessment of a depuration system for their control: assay with tadpoles of Rhinella arenarum (BUFONIDAE) - Navas Romero, Ana Laura (2019)
We evaluated the toxicity of the winery effluent and the efficiency of a symbiotic depuration system by means an experiment with Rhinella arenarum tadpoles. The studied effluent was taken from warehouses during the cleaning season. These effluents subsequently subjected to the purification treatment under evaluation. The effluent samples differentiated into two treatment levels: “raw” where the effluent was evaluated with field conditions and “treated” where the effluent was previously filtered with the symbiotic depuration system. The results of the bioassays compared with the physicochemical parameters determined in the effluent samples. The lethal response had a clear-cut correspondence with the effluent quality assessed utilizing physicochemical parameters. In all cases, dilution of the samples resulted in a significant reduction of their toxicity. It concluded that (a) winery effluents could be harmful to tadpoles of R. arenarum, (b) the symbiotic purification system used to treat wine effluents it would produce a significant reduction in the contaminant levels of the effluent. However, this reduction in contaminant levels does not provide sufficient safety for the release of the effluents into the environment.